CCAFS research and engagement has informed the World Bank-funded US$ 480 million West Africa flagship program to strengthen food system resilience to shocks - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Through active contribution from its West Africa Program, CCAFS Science and Engagement has informed the design of World Bank funded USD480 regional flagship program, the West Africa Food System Resilience Program (FSRP), a 10-year program to strengthen the West Africa food system resilience to shocks led by ECOWAS, CILSS, CORAF. CCAFS has actively contributed to the design and development of the FSRP proposal document and to the production of a blueprint document for a sound implementation planning.